Our Robots, Our Team: Robot Anthropomorphism Moderates Group Effects in Human–Robot Teams - Fraune, Marlena R. (Frontiers in Psychology, 2020)
Past research indicates that people favor, and behave more morally toward, human ingroup than outgroup members. People showed a similar pattern for responses toward robots. However, participants favored ingroup humans more than ingroup robots. In this study, I examine if robot anthropomorphism can decrease differences between humans and robots on ingroup favoritism. This paper presents a 2x2x2 mixed-design experimental study with participants (N = 81) competing on teams of humans and robots. I examined how people morally behaved toward and perceived players depending on players’ Group Membership (ingroup, outgroup), Agent Type (human, robot), and Robot SocialityAnthropomorphism (anthropomorphic, mechanomorphic). Results replicated prior findings that participants favored the ingroup over the outgroup and humans over robots – to the extent that they favored ingroup robots over outgroup humans. This paper also includes novel results indicating that patterns of responses toward humans were more closely mirrored by anthropomorphic than mechanomorphic robots.